Pressures in silo storer of food powders from Eurocode 1 standard (Research, Society and Development, 2021)
Although, studies are being carried out, the determination of the magnitude and distribution of pressure during unloading still presents considerable difficulties, because it is a complex phenomenon in which the pressures depend, among other things and the way the stored material flows. So, the present work using four food products in powder form, and employs the equations given in the standard BS EN 1991/4 (2006) to determine the Asymptote distribution representative of pressures along the body of the silo which features 8 meters high and 2 meters in diameter. This silo, made with smooth steel plates with concentric hopper with inclination of 60° with the horizontal. The flow properties were determined using the Jenike Shear Cell. A similar result was obtained from the pressures between the products cornstarch and potato starch by similarity in particle size. The products under review are cohesive and present no easy flow, however, in none of the cases the pressures of friction along the wall have distinguished themselves between charge and discharge.